Three-dimensional Assisted Autotransplantation of Teeth: Essentials, Outcomes, and Future Implications: A Narrative Review - Fizzah Ikram; Wajiha Maqsood; Leelan Kanwal; Rashna Hoshang Sukhia (Journal of the Pakistan Medical Association, 2026)
Missing teeth is one of the most commonly encountered problems in dental offices globally. With the passage of time, clinicians have developed several methods of treatment for missing teeth. Some of these methods include dental implants, fixed or removable prostheses, and autotransplantation of tooth to the recipient site. Treatment modalities such as prostheses and implants are suitable options for adults because of the presence of mature bone. However, autotransplantation is more favourable for young patients because of continual jaw growth that would accommodate the erupting teeth. Three-dimensional-assisted autotransplantation is one such treatment modality which has significantly surpassed the success and survival rates of conventional autotransplantation while improving ease of handling and simplifying the complex technique sensitive procedure along with better selection of the donor tooth, better pre-operative planning and guided recipient site preparation, decrease in extralveolar time of the donor tooth and decrease in the number of fitting attempts that further limits damage to periodontal cells. In future, robotics and guided surgical methods may help in introduction of minimally invasive procedures. Keywords: Autotransplantation, Missing teeth, 3D technology, Orthodontics.